(untitled) (Malaysian Journal of Learning and Instruction, 2005)
This paper examines the relationship between religiosity level and general self-regulation as well as academic self-regulation. A study was carried out on 23 male and 122 female undergraduate students to examine the relationship between Islamic religiosity level and self-control, procrastination, academic control and academic achievement. Results indicate that religiosity is significantly correlated to all the above factors except for academic achievement. The authors examine the concept of volition or ’will-power’ from the Islamic perspective and compare it with the Western perspective. They further propose an lslamic musabarah scale to measure an individual’s level of volition according to the Islamic perspective.